Analysis on the Dynamic Wave Attenuation Properties of Metaconcrete Considering a Quasi-Random Arrangement of Inclusions - Briccola, Deborah; Pandolfi, Anna (Frontiers in Materials, 2021)
The mitigation properties of metaconcrete cast with two types of resonant inclusions are assessed through wave transmission tests. Three cylindric metaconcrete specimens of regular size (20 cm height, 10 cm diameter), containing an equal number of different type of inclusions disposed in a semi-regular lattice, are tested in the longitudinal direction within the sonic range of frequencies. Inclusions, bi-material spheres consisting of a heavy core coated with a soft material, are characterized by a resonant behavior, evaluated numerically with a finite element modal analysis of a unit metaconcrete cell. Each metaconcrete specimen contains six layers consisting of six engineered aggregates of different type. Inclusions are disposed by rotating each layer with respect to the adjacent ones, as so as to create a pseudo-random arrangement. Specimens are excited by a sinusoidal signal of linearly growing frequency, sweeping a range centered at the translational eigenfrequency of the resonant inclusion. A standard plain concrete specimen is used as reference to define a transmissibility coefficient, that facilitates the quantification of the attenuation properties. With respect to plain concrete, all metaconcrete specimens show a marked (up to 80-90%) attenuation of the transmitted signal in proximity of the numerically estimated eigenfrequency of the inclusion. The intensity of the attenuation is weakly dependent on the type of the inclusion, while the frequency where the attenuation is observed depends markedly on the inclusion type. As a very positive quality in the view of practical applications, experimental results confirm that the attenuation effectiveness of metaconcrete is not related to the ordered microstructural arrangement.